Fiji : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This Selected Issues paper focuses on the insolvency of the National Bank of Fiji (NBF). As of June 1995, an estimated two-thirds of its loan portfolio was judged to be nonperforming (7 1\2 percent of GDP), with slim chances of recovery, leaving the bank with a negative net worth estimated at F USD 170 million. The Reserve Bank of Fiji (RBF) raised concerns about the NBF's lending practices as early as 1991, but it lacked the power to enforce a solution. The problems continued to grow until the NBF's liquidity position finally became untenable in 1994.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet